Determinants of equity pension plan flows - Carmen Pilar Martí Ballester (Kiel Institute for the World Economy (IfW), 2013)
The aim of this study is to analyze investor response to different measures of pension plan performance. To do this, we implement a fixed effects panel data methodology corrected by heteroskedasticity, serial correlation and cross-sectional dependence, as proposed by Vogelsang (Heteroskedasticity, autocorrelation, and spatial correlation robust inference in linear panel models with fixed-effects, 2011). The results obtained show that investors make their decision to invest in a specific pension plan depending on past returns and the type of management company administering the plan. However, participants do not react to risk measures, which may be because they consider all plans making up the equity category to entail the same risk.
Keywords: C23; G23; 330; return; Jensen's Alpha; pension plan flows; panel data models